Hydrogen‐Deuterium Isotope Exchange of Methane via Non‐redox Palladium Catalysis. Issue 6 (19th December 2022) - Kim, Sungah; Ho Lee, Joo; Jarusiewicz, Jamie; Wang, Jen‐Chieh; Woon Jung, Kyung
Abstract: Under mild conditions, Pd(II) catalysts coordinated to tridentate NHC‐amidate‐ether ligand successfully activated the carbon‐hydrogen bond to facilitate the hydrogen/deuterium isotope exchange on methane. The structural features and catalytic behavior suggested an intriguing non‐redox catalytic system derived from the amidate nitrogen. As the amidate nitrogen acts as an internal base, the metal center was able to maintain the oxidation state throughout the reaction. Accordingly, the catalytic system demonstrated its reactivity and stability during the H/D exchange on methane resulting in a high degree of deuterium conversions (44 %) and turnover number (346) under low temperature conditions. Abstract : N‐Heterocyclic carbene (NHC)‐amidate‐ether palladium complexes facilitated C−H activation of methane. These Pd(II) catalysts promoted H/D exchange at relatively low temperatures via a non‐redox catalytic process derived from their amidate functionality.